Using Multilocus Sequence Data To Define the Pneumococcus - Hanage, William P. (American Society for Microbiology, 2005)
We investigated the genetic relationships between serotypeable pneumococci and nonserotypeable presumptive pneumococci using multilocus sequence typing (MLST) and partial sequencing of the pneumolysin gene (ply). Among 121 nonserotypeable presumptive pneumococci from Finland, we identified isolates of three classes: those with sequence types (STs) identical to those of serotypeable pneumococci, suggesting authentic pneumococci in which capsular expression had been downregulated or lost; isolates that clustered among serotypeable pneumococci on a tree based on the concatenated sequences of the MLST loci but which had STs that differed from those of serotypeable pneumococci in the MLST database; and a more diverse collection of isolates that did not cluster with serotypeable pneumococci. The latter isolates typically had sequences at all seven MLST loci that were 5 to 10% divergent from those of authentic pneumococci and also had distinct and divergent ply alleles. These isolates are proposed to be distinct from pneumococci but cannot be resolved from them by optochin susceptibility, bile solubility, or the presence of the ply gene. Complete resolution of pneumococci from the related but distinct population is problematic, as recombination between them was evident, and a few isolates of each population possessed alleles at one or occasionally more MLST loci from the other population. However, a tree based on the concatenated sequences of the MLST loci in most cases unambiguously distinguished whether a nonserotypeable isolate was or was not a pneumococcus, and the sequence of the ply gene fragment was found to be useful to resolve difficult cases.